Analisis Kemampuan Berpikir Analitis Peserta Didik dalam Menyelesaikan Soal Numerasi - Hidayah, Siti Nur; Fauziyah, Nur; Suryanti, Sri (Postulat : Jurnal Inovasi Pendidikan Matematika, 2023)
Analytical thinking is the ability to analyze or solve problems by combining information to solve problems. This study aims to determine students’ analytical thinking skills in solving numeracy problems. The subjects of this study were all students of class VIII-A at MTs Bustanul Arifin Domas Menganti, this study used a descriptive quantitative method. The instrument used is a description test with 3 questions. Based on the results of the research, it is known that students’ analytical thinking skills in solving numeracy questions are in the medium category. 73.53%, and there are 7 students in the low category with a percentage of 20.59%.